Implementation of the Land and Building Tax Amnesty Program: A Case Study Analysis at the Regional Tax Service Agency - Al Rasyid, Husain Ibrahim; Rodiyah, Isnaini (Indonesian Journal of Public Policy Review, 2023)
This qualitative descriptive study investigates the implementation of the Land and Building Tax (PBB) exemption program in Sidoarjo Regency, focusing on communication, resources, disposition, and bureaucratic structure. Employing purposive sampling, primary data was gathered through observation, interviews, and documentation. Utilizing Miles and Huberman's data analysis, the study reveals that all variables were fulfilled, with challenges arising from insufficient information dissemination by some villages and a shortage of billing staff. The Sidoarjo Regional Tax Service Agency (BPPD) is urged to innovate communication channels for direct community engagement and enhance staffing levels. This research provides valuable insights for policymakers and tax authorities globally, emphasizing the need for efficient communication strategies and resource allocation to ensure successful tax exemption programs. Highlight : Effective Communication: The study underscores the crucial role of communication in the successful implementation of the Land and Building Tax (PBB) exemption program, emphasizing the need for streamlined information flow between villages and residents. Resource Allocation: The research highlights challenges stemming from a shortage of billing staff in Sidoarjo Regency, emphasizing the significance of adequate resource allocation to ensure the smooth operation of tax exemption policies. Policy Implications: The findings provide actionable insights for tax authorities and policymakers globally, emphasizing the importance of efficient communication strategies and resource management in optimizing the effectiveness of land and building tax exemption programs. Keywords: Land and Building Tax, Exemption Program, Implementation, Sidoarjo Regency, Communication